152k views
5 votes
Explain how you got the answer

Explain how you got the answer-example-1
User DarkDeny
by
5.0k points

1 Answer

2 votes

Answer:


\huge\boxed{Center = (3,3),Radius = 2√(15) }

Explanation:

Given equation is


x^2 + y^2 -6x-6y -42 = 0

Adding 42 to both sides


x^2 + y^2 -6x-6y = 42\\

Completing squares


x^2 -6x+y^2 -6x = 42\\(x)^2 - 2(x)(3) +y^2 - 2(y)(3) = 42

Adding (3)² => 9 and (3)² => 9 to both sides


(x-3)^2+(y-3)^2 = 42+9+9\\(x-3)^2 + (y-3)^2 = 60\\(x-3)^2 (y-3)^2 = (2{√(15))^2}

Comparing it with
(x-h)^2+(y-k)^2 = r^2 where Center = (h,k) and Radius = r

We get:

Center = (3,3)

Radius =
2√(15)

User Keigo
by
5.9k points